The Long-Term Efficacy of Neoadjuvant Chemotherapy Followed by Radical Hysterectomy Compared With Radical Surgery Alone or Concurrent Chemoradiotherapy on Locally Advanced-Stage Cervical Cancer. Issue 1 (1st January 2011) - Yin, Mingzhu; Zhao, Falin; Lou, Ge; Zhang, Haiyu; Sun, Meng; Li, Cong; Hou, Yan; Li, Xia; Meng, Fanling; Chen, Xiuwei
Abstract : Objectives: The purpose of this study was to compare the long-term survival of patients with locally advanced cervical cancer (stages IB2-IIB) treated with neoadjuvant chemotherapy followed by radical hysterectomy (hysterectomy plus pelvic lymph node dissection) (NACT + RS) with the survival of those treated with radical surgery (hysterectomy plus pelvic lymph node dissection) (RS) or concurrent chemoradiotherapy (CCRT). Methods: A retrospective study was performed. Patients were followed up for 54 to 114 months (median, 82.8 months). All risk factors that may have affected the disease-free survival (DFS) and overall survival (OS) were assessed. Results: From January 2000 to December 2005, 476 eligible patients were followed up. The 5-year DFS rates of the NACT + RS, RS, and CCRT groups were 85.00%, 77.44%, and 52.94%, respectively ( P < 0.0001), whereas the 5-year OS rates were 88.67%, 80.21% and 64.37%, respectively ( P < 0.0001). The NACT + RS group had significantly higher survival rates than both the RS (DFS: hazard ratio = 1.870, P = 0.0031; OS: hazard ratio = 1.813, P = 0.0175) and CCRT (DFS: hazard ratio = 3.535, P < 0.0001; OS: hazard ratio = 3.157, P < 0.0001) groups, while adjusting for the pathological type, clinical stage, tumor size (initial), and age. The 5-year DFS rate for patients receiving TP (paclitaxel and cisplatin) was 90.55%, and 71.70% for patients receiving PVB (cisplatin, vincristine, and bleomycin); the 5-year OS rates were 96.75% for TP and 70.09% for PVB, respectively. Patients receiving TP had a statistically significant improvement in both 5-year DFS and OS rates ( P < 0.001). Conclusions: Neoadjuvant NACT + RS improves the long-term DFS and OS of patients with locally advanced cervical cancer stage IB2-IIB compared with RS alone and especially compared with CCRT. In the NACT + RS group, NACT with TP improves the long-term DFS and OS of patients compared with patients who had PVB chemotherapy regimen. These results may provide some useful information for clinicians to treat patients with locally advanced cervical carcinoma.